Stiffness Prediction of 17 Years Aged Mangium (Acacia mangium Willd) By Non-Destructive Testing - Dwi J Priyono; Surjono Surjokusumo; Yusuf Sudo Hadi; Naresworo Nugroho (Masyarakat Peneliti Kayu Indonesia, 2011)
Non-destructive test of mechanical properties of wood is an alternative methode which it is done without damaging the wood. The study tried to find the relationship between wood stiffness through non-destructive with MoE estimation. The 17 years mangium wood beam were tested both in the sorts of sample beam and small clear specimen. Beams were tested by ultrasonic wave propagation using Sylvatest- Duo NDT equipment and Panter Timber Sorting Machine, while destructive testing using Shimadzu UTM. The small clear specimen tested using Sylvatest-Duo equipment, while it’s destructive using Instron UTM. Destructive test were according to ASTM D 143-94 (2008) for the small clear specimen (scs), while ASTM D 198-05a (2008) applied for the beam samples. The results showed that the scs sample with 14.7% moisture content and density of 0.61 gr cm-3 have ultrasonic wave propagation velocity (V) of 5,764 m s-1, the dynamic modulus of elasticity (MoEd) and static (MoEs) each for 243,933 and 104,004 kg cm-2, while the value of static flexural strength (MoRs) was 889 kg cm-2. For the beam sorts with 15.4% moisture content and density of 0.58 g cm-3 has a velocity of ultrasonic waves propagation at 4,944 m s-1, the value of MoEd and MoEs respectively 167,357 and 51,780 kg cm-2, while the value of MoRs was 449 kg cm-2. The beam MoRs and MoEs values which resulted by Panter (called MoEp and MoRp) were 146,756 and 538 kg cm-2 respectively. Through simple linear regression equations were discovered relationships on eight prediction equations that can be considered good to use.Key words: beams, MoE-dynamic, MoE-static, non-destructive testing, prediction equation, small clear specimen.